Sūq Geertz on the Market - Geertz, Clifford (2023)
A formative ethnography of the relationship between markets and social life, back in print. Originally published in 1979, Clifford Geertz's essay on the Moroccan bazaar is a classic ethnographic account of the interplay of economic, social, and religious lives in the bustle of transaction. Drawing on years of fieldwork in the Middle Atlas town of Sefrou, Geertz explores how actors from diverse backgrounds assess the worth and meaning of other people's wares, words, and ways of doing business. He shows how the search for market information, so central to the theorization of markets by economists, is here based on careful appraisals of social relations, embedded in understandings of the broader institutional environment of the market town and its hinterlands. With a richness of insights procured for generations of readers, Geertz's essay on the sūq is a model of and for the craft of ethnographic theory. Long out of print, it is republished here in a stand-alone edition introduced by Lawrence Rosen.